2023
DOI: 10.1126/sciadv.ade7701
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Kondo lattice in doped MoTe 2 /WSe 2 bilayers

Abstract: We theoretically study the interplay between magnetism and a heavy Fermi liquid in the AB-stacked transition metal dichalcogenide bilayer system, MoTe 2 /WSe 2 , in the regime in which the Mo layer supports localized magnetic moments coupled by interlayer electron tunneling to a weakly correlated band of itinerant electrons in the W layer. We show that the interlayer electron transfer leads to a chiral Kondo exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This represents a design principle for creating and realizing new forms of quantum criticality and associated strange metallicity: The cooperation of strong correlations, large spin–orbit coupling, and crystalline symmetry represents a robust means to create varied local degrees of freedom; and the tuning of such strongly correlated systems can realize a sequence of beyond-Landau quantum critical points. Beyond heavy fermion metals, effective local degrees of freedom have also been advanced for pertinent molecular orbitals of d -electron-based flat band systems ( 38 41 ) and for moiré states of twisted structures ( 42 44 ). Thus, we expect this design procedure to operate not only in multipolar heavy fermion metals but also in transition-metal compounds, synthetic systems such as moiré structures, and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a design principle for creating and realizing new forms of quantum criticality and associated strange metallicity: The cooperation of strong correlations, large spin–orbit coupling, and crystalline symmetry represents a robust means to create varied local degrees of freedom; and the tuning of such strongly correlated systems can realize a sequence of beyond-Landau quantum critical points. Beyond heavy fermion metals, effective local degrees of freedom have also been advanced for pertinent molecular orbitals of d -electron-based flat band systems ( 38 41 ) and for moiré states of twisted structures ( 42 44 ). Thus, we expect this design procedure to operate not only in multipolar heavy fermion metals but also in transition-metal compounds, synthetic systems such as moiré structures, and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments ( 38 , 39 ) have motivated the idea ( 40 , 41 ) that, through molecular orbitals (of limited spatial extent), Kondo effects develop as a proper description of the low-energy physics even for d -electron-based flat band systems. Meanwhile, in twisted graphene structures, there have been proposals for their understanding in terms of Kondo effects that are associated with the degrees of freedom of moiré unit cells ( 42 44 ). In these systems, different kinds of crystalline symmetries or stacking/twisting in different types of flat bands can yield various forms of local degrees of freedom.…”
mentioning
confidence: 99%
“…As a result, IXs have lifetimes in the tens to hundreds of nanoseconds, much higher than that of intralayer excitons. These properties have resulted in an explosion of interest in IXs in fields such as excitonic transport, Bose-Einstein condensation [36][37][38], and excitonic insulator [41][42][43]. Recent studies have shown that applying either an in-plane or out-of-plane electric field to TMDs monolayers can lead to a significant impact on their excitonic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of electronic orders in two-dimensional (2D) materials establishes a rich platform for the emergence of new physics. Since the isolation of van der Waals monolayers, a variety of magnetic orders have been observed in the 2D limit, including ferromagnetic, , quantum spin-liquid candidates, , and multiferroic order. , Furthermore, exploring the unique degrees of freedom of van der Waals materials, namely, the easy and clean stacking of layers forming heterostructures and introducing twist angles between layers, has allowed the emergence of new magnetic orders, including orbital ferromagnets , and heavy-fermion Kondo lattice materials. The recent isolation of CeSiI in the ultrathin limit establishes heavy-fermion Kondo insulators as a new member in the family of van der Waals building blocks.…”
mentioning
confidence: 99%
“…In the realm of van der Waals materials, heavy-fermion systems have been artificially engineered in heterostructures with different 2D materials including 1T–1H TaS 2 bilayers, MoTe 2 /WSe 2 bilayers, and MoS 2 bilayers. ,, Now, monolayer CeSiI brings Kondo physics to a single van der Waals block, allowing us to study these systems from a novel perspective combining typical surface-science experimental techniques such as scanning tunneling microscopy and exploiting the degrees of freedom characteristic of van der Waals materials . However, theoretical studies on monolayer CeSiI are still scarce due to the difficult treatment of Kondo systems from an ab initio perspective.…”
mentioning
confidence: 99%